The Clown of God: An Old Story - DePaola, Tomie (New York : Harcourt Brace Jovanovich, 1978)
A once-famous Italian juggler, now old and a beggar, gives one final performance before a statue of Our Lady and the Holy Child.
Keywords: Legends -- Italy; Jugglers -- Fiction; Folklore -- Italy; Jugglers and juggling -- Fiction; Clowns -- Fiction